Finland : Financial System Stability Assessment Update. (IMF Staff Country Reports; Country Report ;, 2010)
The Finnish financial sector has weathered during the global crisis. Banks' capital buffers were sufficient, but liquidity and credit risks required monitoring. The study assessed that there is a need for strong crisis management framework. It is found that an evaluation of Deposit Guarantee Fund (DGF) using Core Principles for Effective Deposit Insurance Systems would support reform efforts. Banking supervision is robust, and follows relevant EU Directives and the Basel Core Principle (BCP) for Effective Banking Supervision closely. The Financial Supervisory Authority (FIN-FSA) has implemented the 2001 Financial Sector Assessment Program (FSAP) recommendations, but challenges remain.